Pokazannikova – Maximal and repeated muscular efforts: ergometric and physiological evaluation criteria - Samborskiy, A.G.; Pakhomova, L.E.; Shipulin, G.Y.; Pokazannikova, L.T. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to analyze strength control patterns for isometric contractions of the rectus femoris in a weightlifting model testing experiment by repeated 5-second maximal strength tests and 1-minute maximal strength keeping tests. Methods and structure of the study. We sampled for the strength training system testing experiment the 18-20 years old elite sambo fighters (n=8, Candidate Masters of Sports and Masters of Sports) 174-182cm tall and 66-82 kg heavy. The tests were run in laboratory using a pressure platform. Results and conclusion. The pre- versus post-experimental 5s maximal strength tests of the isometric contractions of rectus femoris found significant progress in the following test rates: peak force by 10.4%; maximal strength by 13.3% and force impulse by 15.5%. The pre- versus post-experimental 1min maximal strength keeping tests found significant progress in the following test rates: peak force by 11.2%; maximal strength by 15.2%; maximal strength reaching time by 14.6%; and the 97% maximal strength reaching time by 15.8%. The strength variation analysis found significant progress in the maximal strength, maximal strength reaching and keeping times with the maximal strength control and fall patterns.